2021
DOI: 10.48550/arxiv.2109.12005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of local arrangement of Fe and Ni on the phase stability and magnetocrystalline anisotropy in Fe-Ni-Al Heusler alloys

Abstract: On the basis of density functional calculations, we report on a comprehensive study of the influences of atomic arrangement and Ni substitution for Al on the ground state structural and magnetic properties for Fe2Ni1+xAl1−x Heusler alloys. We discuss systematically the competition between five Heusler-type structures formed by shuffles of Fe and Ni atoms and their thermodynamic stability. All Ni-rich Fe2Ni1+xAl1−x tend to decompose into a dual-phase mixture consisting of Fe2NiAl and FeNi. The successive replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 62 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…However, Neibecker et al [41] recently suggested that layered crystal motives can be a strong competitor. This is corroborated by our recent efforts devoted to the firstprinciples study of structural stability and magnetic properties of these motifs in (Fe,Co) 2 Ni 1+x Al 1−x [42], [43]. In particular, we identified the T p -layered structure with nearly cubic lattice parameters as a potential ground state for Febased alloys at the stoichiometric composition and small Niexcess, whereas stoichiometric Co 2 NiAl has in turn an inverse tetragonal structure with c/a = 1.3.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…However, Neibecker et al [41] recently suggested that layered crystal motives can be a strong competitor. This is corroborated by our recent efforts devoted to the firstprinciples study of structural stability and magnetic properties of these motifs in (Fe,Co) 2 Ni 1+x Al 1−x [42], [43]. In particular, we identified the T p -layered structure with nearly cubic lattice parameters as a potential ground state for Febased alloys at the stoichiometric composition and small Niexcess, whereas stoichiometric Co 2 NiAl has in turn an inverse tetragonal structure with c/a = 1.3.…”
supporting
confidence: 70%
“…Inverse XA structure: two X atoms are placed at non-equivalent 4a (0, 0, 0) and 4c (1/4, 1/4, 1/4) sites and have different environments, while Ni and Al are placed at 4b (1/2, 1/2, 1/2) and 4d (3/4, 3/4, 3/4) positions, respectively. T p , T c , and T # can be constructed from the inverse structure by intermixing [41], [42].…”
Section: Details Of the Calculationsmentioning
confidence: 99%
See 3 more Smart Citations